IMPACT OF VISUAL AIDS AND PICTORIAL IMAGES ON CREATIVE WRITING SKILL OF ESL STUDENTS AT SECONDARY LEVEL - Imdad Hussain; Dr. Perveen Akhter Farhat; Dr. Ghulamullah (International Journal of Contemporary Issues in Social Sciences, 2023)
The present study is determining the impact of visual aids and pictorial images on the creative writing of ESL learner in Pakistani context. The research was conducted in a public sector high school of district Lahore during summer vacations. For ethical consideration institute name was not mentioned. Using purposive sampling technique, the researchers selected sixty students of ninth class and divided them in two equal groups, named controlled and experimental groups, the earlier was treated in traditional style and the later was treated by means of visual aids and pictures. The treatment period was contained on three months three hours daily. The data was composed by using pretest and posttest methods, the collected data was later analyzed by using SPSS software latest version. The analyzed data was presented in tables. The posttest results showed significant difference in the scores of both groups, as experimental group performed better than controlled group, while in pretest their score was almost same. The results suggested that visual aids and pictures improved the creative writing of these students, and it’s better than traditional style of learning. In nutshell the research will instigate to the educators for employing new approaches in English language learning.